(untitled) (Scientia Agropecuaria, 2023)
Cucurbitaceae species constitute a family with a wide worldwide distribution and great nutritional and medicinal importance. The Cucurbita genus is the most important of the family with valuable species such as C. maxima and C. moschata. However, the large-scale production of sex specific plants using the conventional propagation methods has various limitations. The tissue culture such as micropropagation can help overcome these limitations. The aim of this study was to establish a protocol for ex vitro and in vitro clonal propagation of two varieties of Cucurbita moschata: ‘loche’, a variety of commercial vegetative propagation and endemic in Lambayeque, and ‘chuyán’ another variety of very restricted cultivation in some Andean regions of the north of the Peru. Likewise, the in vitro propagation of ‘chisguín’ (C. ecuadorensis), a threatened endemic wild species from the coast of Ecuador. ‘Loche’ was propagated ex vitro by microcutting with a node and leaf, and micropropagated in MS culture medium supplemented with 0.02 mg L-1 IAA and 0.02 mg L-1 GA3. Seedlings of ‘chuyán’ and ‘chisguin’ were micropropagated in MS with with 0.02 mg L-1 IAA, 0.5 mg L-1 BAP and 0.02 mg L-1 GA3. This study constitutes the first report on micropropagation of Peruvian and Ecuadorian varieties and species of the Cucurbita genus.